Measuring executive function after yoga for adults with acquired brain injury: a pilot study - Grieb, Emily, author; Schmid, Arlene, advisor; Stephens, Jaclyn, committee member; Riggs, Nathaniel, committee member (Colorado State University. Libraries, 2022)
Background: Acquired brain injury (ABI) may result in cognitive impairments, particularly deficits in executive function (EF), which may impact engagement in everyday activities. Yoga has been shown to improve various health outcomes for individuals with ABI. This study aims to explore the impact of group yoga on EF for individuals with ABI. Methods and Materials: This was a single-arm pilot study that involved eight weeks of therapeutic group yoga led by a registered yoga teacher. Nine participants attended hour-long, in-person yoga classes once a week. Sessions included seated, standing, and floor postures combined with breathwork and meditation. EF was assessed pre- and post-intervention using the Behavior Rating Inventory of Executive Function for Adults (BRIEF-A) self-report form. Results: The behavioral regulation index improved significantly pre to post yoga. No significant improvements were found on the EF scales, metacognition index, or global executive composite. However, measurable improvements (>5%) were found in the following EF scales: Emotional Control, Plan/Organize, and Organization of Materials. Conclusion: Group-based yoga may improve behavioral regulation for adults with chronic ABI, however further research is needed.
Keywords: cognition; stroke; yoga; executive function; acquired brain injury; traumatic brain injury